Revisiting the craniosynostosis-radial ray hypoplasia association: Baller-Gerold syndrome caused by mutations in the RECQL4 gene - Van Maldergem, L; Siitonen, H A; Jalkh, N; Chouery, E; De Roy, M; Delague, V; Muenke, M; Jabs, E W; Cai, J; Wang, L L; Plon, S E; Fourneau, C; et al. (Journal of medical genetics, 2006)
Baller-Gerold syndrome (BGS) is a rare autosomal recessive condition with radial aplasia/hypoplasia and craniosynostosis (OMIM 218600). Of >20 cases reported so far, a few appear atypical and have been reassigned to other nosologic entities, including Fanconi anaemia, Roberts SC phocomelia, and Pfeiffer syndromes after demonstration of corresponding cytogenetic or molecular abnormalities. Clinical overlap between BGS, Rothmund-Thomson syndrome (RTS), and RAPADILINO syndrome is noticeable. Because patients with RAPADILINO syndrome and a subset of patients with RTS have RECQL4 mutations, we reassessed two previously reported BGS families and found causal mutations in RECQL4 in both. In the first family, four affected offspring had craniosynostosis and radial defect and one of them developed poikiloderma. In this family, compound heterozygosity for a R1021W missense mutation and a g.2886delT frameshift mutation of exon 9 was found. In the second family, the affected male had craniosynostosis, radial ray defect, poikiloderma, and short stature. He had a homozygous splice site mutation (IVS17-2A>C). In both families, the affected offspring had craniosynostosis, radial defects, and growth retardation, and two developed poikiloderma. Our results confirm that BGS in a subgroup of patients is due to RECQL4 mutations and could be integrated into a clinical spectrum that encompasses RTS and RAPADILINO syndrome.